The Role of Parents in Forming The Self- Concept of Children with Special Needs when Interacting in The Community - Maria Kezia Vania; Siti Meisyaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
In essence, humans are social beings where they need each other to interact and communicate. This is also needed by children with special needs even though they have significant differences in terms of physical, psychological, cognitive and social which makes it take a longer time and process to understand something and achieve life goals. This research was conducted to determine the role of parents in forming self-concept, providing motivation, and increasing the confidence of children with special needs when interacting in the community. This research was carried out based on social interaction theory as the research basis. When humans interact there is interpersonal communication, namely communication between two or more people directly where the sender and receiver of messages can exchange messages directly. The research subjects were three mothers of children with special needs with mental retardation, namely children who have significantly below average intelligence and behavioral inability to adapt during development. This research method is descriptive qualitative with data collection techniques directed interviews and documentation. Parents admit that educating them requires more patience, process, and time than children in general. The results of the research through interviews show that the role of parents is carried out in a concrete way by encouraging children to want to learn, be independent and interact with others and tell what is good and bad. So it was concluded that the role of parents is very important in forming self-concept, giving motivation and confidence to children with special needs when interacting in the community.